Dapatkah Budaya Organisasi Memoderasi Hubungan antara Motivasi dan Kinerja Auditor pada Kantor Akuntan Publik di Indonesia? - Jannah, Izzatul (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
A good quality audit is certainly the result of a good audit performance. Therefore, it is important to know the factors that influence auditor performance. This research examines whether auditor motivation can affect their audit performance and whether organizational culture can moderate auditor motivation toward their audit performance. This research uses a quantitative method with data sources in the form of questionnaire results from 196 auditors of Public Accounting Firms in Indonesia. The data in this research were processed using the PLS-SEM model with the help of SmartPLS 4 software. The research's results indicate that motivation significantly positively affects auditor performance, and organizational culture can moderate the relationship between motivation and auditor performance.